Continuous Biosorption of Pb2+ with Bamboo Shoots (Bambusa spp.) using Aspen AdsorptionÂ® Process Simulation Software - Mc Lein Roger M. Lubiano II; Cris Vincent L. Manacup; Allan N. Soriano; Rugi Vicente C. Rubi (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
The health risks impact of heavy metal contamination in the environment has prompted researchers to study its mitigation in an efficient and cost-friendly approach.Â Recently, simulated continuous biosorption using agricultural wastes is gaining popularity because it offers cheaper and faster alternative study methods using efficient large-scale removal of lead, which is known to cause adverse effects even at low concentrations. Bamboo shoots (Bambusa spp.), a delicacy known in Southeast Asia, are recognized worldwide, but the inedible sheath husks are thrown. This study evaluated the continuous Pb2+ biosorption performance of Bambusa spp. using Aspen Adsorption V8.4 by varying bed height, influent concentration, and volumetric flow rate. Linear driving force model was used to simplify, according to a separate batch biosorption study, ion exchange mechanism and Langmuir isotherm for equilibrium conditions. The backward differencing method was used to solve the resulting differential equation. Results showed that increasing the volumetric flowrate from 4.00x10-5 to 8.00x10-5 m3/s, the bed height from 0.2 to 1.0 m, and influent concentration from 80 to 120 ppm resulted in changes in the breakthrough time by a factor of 0,5, 4.0, and 0.67 respectively. Analysis of the breakthrough curves showed that increasing volumetric flow rate shortens breakthrough time due to reduced contact time, and increasing Pb2+ concentration facilitated ion exchange by increasing concentration difference. Bed height provides more binding sites available hence, higher Pb2+ removal.